PENGARUH PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PT BARATA INDONESIA TAHUN 2009-2011 - Irwanti, Novika; Rinaldi, Rinaldi; Eriswanto, Elan (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2020)
This study aimed to determine the effect of the level of account receivable turnover on profitability in PT Barata Indonesia in 2009-2011. Variables used in this study is accounts receivable turnover, and profitability. This research method in this study is a quantitative method, a sample of 36 financial statements of PT Barata Indonesia for the years 2009-2011. For receivables turnover can be seen with the testing criteria that if tcount>ttable (5,372>2,028) then H0 is rejected Ha accepted. To see the significance , visible results ttable statistic at a significance level of 5% sig = 0,000 > 0,05 significance level 0,05 (5%). The result show that the influence turnover partially and simultaneously affect the profitability of PT Barata Indonesia (Persero).